2017
DOI: 10.1016/j.nicl.2017.02.025
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-induced abnormal cortical thickness in patients with nasopharyngeal carcinoma after radiotherapy

Abstract: Conventional MRI studies showed that radiation-induced brain necrosis in patients with nasopharyngeal carcinoma (NPC) in years after radiotherapy (RT) could involve brain gray matter (GM) and impair brain function. However, it is still unclear the radiation-induced brain morphological changes in NPC patients with normal-appearing GM in the early period after RT. In this study, we acquired high-resolution brain structural MRI data from three groups of patients, 22 before radiotherapy (pre-RT) NPC patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
42
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 66 publications
9
42
1
Order By: Relevance
“…The method of PCA+SVM was quite helpful to improve the accuracy of the classification, and validly detected the abnormal brain regions, which widely contained the previous research achievement. As shown in Table 1, our results were consistent with previous studies, suggesting that the method was in favour of identifying the injury caused by RT [5][6][7]9]. The classification accuracy was 82.5 %, indicating that the method could well identify the abnormal changes induced by RT.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The method of PCA+SVM was quite helpful to improve the accuracy of the classification, and validly detected the abnormal brain regions, which widely contained the previous research achievement. As shown in Table 1, our results were consistent with previous studies, suggesting that the method was in favour of identifying the injury caused by RT [5][6][7]9]. The classification accuracy was 82.5 %, indicating that the method could well identify the abnormal changes induced by RT.…”
Section: Resultssupporting
confidence: 90%
“…Previous studies have found that radiation therapy for NPC resulted in multiple regions abnormalities, such as temporal lobe necrosis [3,4], precuneus, cuneus, lateral occipital cortex [5], the vermis, hippocampus, cerebellum lobule, middle occipital lobe, and insula [6,7]. However, it was difficult for doctors to identify the abnormal changes after radiotherapy (RT) based on original image features.…”
Section: Introductionmentioning
confidence: 99%
“…One theory is that the damage of vascular endothelial cells follows local brain tissue ischemia of the whole brain [26]. Larger scale, nonlocalized injury of the brain may be induced by RT due to central nervous system autoimmune vasculitis [11]. Evaluation of the irradiated temporal microstructural damage at acute reaction and early delayed stages is essential to help with adjusting treatment protocols.…”
Section: Discussionmentioning
confidence: 99%
“…Given that macro/micro-structural changes in the brain underlie neurocognitive impairment, this research study is motivated by the hypothesis that MRI deduced micro and macrostructural changes can provide insights on detecting temporal lobe injury in RT treated NPC patients more sensitively than the established neurocognitive score. There are three phases of the pathophysiological reaction to irradiation in normal brain tissue: the acute reaction period (few days to few weeks), early delayed radiation period (1-6 months), and late delayed radiation period (6 months to few years) [10,11]. Lv et al [12] found that time-dependent volumetric decreases for the total gray matter (GM) of the bilateral temporal lobe, as well as time-dependent ventricle expansion in NPC patients through acute reaction period to delay radiation period.…”
Section: Introductionmentioning
confidence: 99%
“…The delayed effects of radiation damaged a range of structures, including the nervous system, bone, major vessels, mucus membranes, pituitary and salivary glands, as well as increasing the risk of radiation-induced neoplasms [11]. The cortical thickness altered in different period (eg, acute reaction period (few days to few weeks), early delayed radiation period (1-6 Nasopharyngeal Carcinoma months), and late delayed radiation period (6 months to few years)), and this alterations were dynamic [12]. In terms of functional connectivity, a prior study found that the RT might induce functional connectivity impairments in NPC patients, which resulted in the cognitive impairments, especially the attention alterations [13].…”
Section: Introductionmentioning
confidence: 99%